The Housing-Climate Nexus: How Planning and Wildfire Drive Displacement in the Central Okanagan, British Columbia - Oscilowicz, Emilia; Chapple, Karen; Connolly, James J. T.; Cordingley, Connor (Canadian Planning and Policy / Aménagement et politique au Canada, 2026)
This article examines the intersecting dynamics of wildfire-driven displacement and housing pressures in the Central Okanagan region of British Columbia. Drawing on quantitative mobility data and semi-structured interviews with planners, housing advocates, and insurance professionals, we explore how housing affordability and climate crises exacerbate each other. Findings reveal a compounding housing-climate nexus: as climate disasters displace residents, housing unaffordability and the dynamics of land use planning in the region complicate wildfire disaster. We call for integrated planning and policy responses that address both housing affordability and climate resilience and highlight the urgent need for short- and long-term planning reforms alongside cross-sectoral collaboration.